Development and implementation on torsional vibration measurement of rotational machinery's shaft. Issue 1 (July 2021) - Yang, Zixuan; Wang, Zhifang; Wang, Xuan
Abstract: The measurement and analysis on torsional vibration is an important aspect to research the performance state of rotating machinery's shaft. This paper introduces the basic procedure of torsional vibration measurement, deduces the manifestation of torsional vibration signal, focuses on the hardware design and software implementation of torsional vibration measurement system, and applies the measurement system to a certain type of ship and steam turbine generator shaft in actual testing. The measurement results verify the practicability and accuracy of the system.